Peningkatan efisiensi energi melalui optimasi cycle steam boiler pada operasi boiler: studi kasus di PT. Kaltim Methanol Industri (KMI) - Wingo Wira Dewanatan; Muhammad Kurniawan Adiputra; Indra P. Hakim; Asep Zainuddin; Imam Karfendi Putro; Rochim Bakti Cahyono (Jurnal Rekayasa Proses, 2020)
Methanol is one of the important intermediate chemicals which is used widely in many processes to produce final products such as formaldehyde, dimethyl ether (DME), dimethyl terephthalate (DMT), and methyl tertiary butyl ether (MTBE). As a pioneer of methanol producer in Indonesia, PT. Kaltim Methanol Industri (KMI) has a strong commitment for sustainability and saving natural resources including enhancement of energy efficiency during production activities. Since mid-2018, to fulfill the electricity needs, PT. KMI has two main sources of electricity namely internal source using steam turbine generator and tie-in from PT. Kaltim Daya Mandiri (KDM). The modification of electricity sources promotes PT. KMI to evaluate the efficiency of internal electricity production. This has been conducted by performing optimization of blow down rate or cycle steam in boiler operation. Based on the data logbook, this work aims to evaluate the effect of blowdown rate on the energy saving and natural gas consumption. When the number of cycle steam boilers is altered from around 10 to 24, the company could get the potential energy saving around 300 MMBTU/day or 7.14% of total based energy consumption. In the boiler operation, decreasing blowdown rate would raise the cycle steam boiler and give final consequences to reduce energy losses from the release of BFW. The optimization of this cycle steam also cut the boiler specific energy consumption into around 3.0 MMBTU/ton steam. Based on the average heating value, this innovation could decline the natural gas consumption of PT. KMI around 122.91 MMSCF in the period of July 2018 – July 2019. Based on the result above, the modification of the cycle steam boiler would enhance energy efficiency, saving the natural resources and promote the application of sustainable development concept in the chemical industry.